Mosby's physical examination DVD series : DVD 10 : abdoment [ - Ball, Jane; Benedict, G. William; Dains, Joyce E.; Seidel, Henry M. (Mosby's physical examination DVD series, 2006)
"This 14 minute video shows the steps needed to examine abdominal organs and structures, plus the proper use of equipment. With the patient supine, it demonstrates how to inspect, auscultate, palpate, and percuss the abdomen and how to locate findings within four quadrants or nine regions. With the patient seated, it presents fist percussion over the kidneys. The video shows expected findings in adults and ways to modify techniques and identify age-related findings in pediatric and geriatric patients. In addition, it identifies bowel sounds on auscultation as well as tympany and dullness on percussion."--Publisher's website